Addressing the shortage of pathologists in Africa: Creation of a MMed Programme in Pathology in Zambia - Victor Mudenda; Evans Malyangu; Shahin Sayed; Kenneth Fleming (AOSIS, 2020)
Background: With approximately one pathologist for one million people compared to ratios of approximately 1 to 25 000 in the United States and United Kingdom, there is a severe shortage of pathologists in much of Africa. The situation is particularly severe in Zambia, where, in 2009, the ratio was 1 to 1.4 million. Objective: To address this, a postgraduate Master of Medicine (MMed) training programme was launched in Lusaka in 2011. Methods: The process and most significant challenges and lessons learned were documented, as they may be of value to other countries facing similar challenges. Results: Since 2011, four Zambian pathologists have graduated, doubling the number of indigenous pathologists in the country. Currently 10 students are in training. The most significant problem was issues arising from the split responsibilities of the Ministries of Health and of Education and the most important lesson learned was the crucial need for broad local ownership and commitment. Conclusion: Successfully addressing the shortage of local pathologists by creating country-specific, postgraduate MMed training programmes, even in situations of restricted resources, is feasible. However, having access to and support from the shared resources, expertise and knowledge of a regional College of Pathologists would be a major advantage.